Audit of medical (non-targeted) liver biopsy specimen quality, pathology reporting and effect on patient management. Issue 7 (26th May 2021) - Seth, Sidhant; Forrest, Ewan H; Morris, Judith M; Heydtmann, Mathis; Konanahalli, Prakash; Kohnen, Gabriele; Oien, Karin A
Abstract : Aims: To evaluate our medical liver pathology practice and its influence on patient management, using audit templates published by the UK Royal College of Pathologists (RCPath). Methods: We audited medical liver biopsies reported in our centre in 2019 using RCPath proformas. Data were collected from pathology reports and corresponding electronic patient record. Results: 60 cases were selected for audit from 135 eligible biopsies reported in 2019. 58/60 cases were core biopsies and 2/60 were laparoscopic wedge biopsies. 53/57 (93%) core biopsies with available data met RCPath adequacy criteria (length >15 mm and/or ≥6 portal tracts). Most reports (57/60; 95%) were judged to have helped patient management. 25/60 (42%) biopsy reports helped to clarify the clinical diagnosis and 48/60 (80%) led to altered management. Conclusions: We demonstrate the utility of the RCPath audit templates, highlighting the clinical value of medical liver biopsies in the diagnostic work-up and management of patients with liver disease.